2009
DOI: 10.3181/0812-mr-365
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Epithelial-Mesenchymal Transition in Palatal Fusion

Abstract: During palatal fusion, the midline epithelial seam between the palatal shelves degrades to achieve mesenchymal confluence. Morphological and molecular evidence support the theory that the epithelial-mesenchymal transition is one mechanism that regulates palatal fusion. It appears that transforming growth factor (TGF)-beta signaling plays a role in palatal EMT. TGFbeta3 is the main inducer in palatal fusion and activates both Smad-dependent and -independent signaling pathways, including the key EMT transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 108 publications
3
38
0
Order By: Relevance
“…Apoptotic and migratory processes are well-known important mechanisms to explain MES degeneration (Carette and Ferguson 1992;Mori et al 1994;Taniguchi et al 1995;Cuervo and Covarrubias 2004;Vaziri Sani et al 2005). However, another major mechanism that has been strongly proposed to explain MES degeneration is the EMT (Griffith and Hay, 1992;Shuler et al 1991Shuler et al , 1992Kaartinen et al 1997;Nieto 2002;Nawshad et al 2004;Jin and Ding 2006;Yu et al 2009). We identified the molecular interaction between miR200b and Tgf-b-mediated Smad2 and Snail by reporter assay and overexpression of miR-200b.…”
Section: Mir-200b Modulates E-cadherin and Tgf-b-mediated Smad2 And Smentioning
confidence: 97%
See 1 more Smart Citation
“…Apoptotic and migratory processes are well-known important mechanisms to explain MES degeneration (Carette and Ferguson 1992;Mori et al 1994;Taniguchi et al 1995;Cuervo and Covarrubias 2004;Vaziri Sani et al 2005). However, another major mechanism that has been strongly proposed to explain MES degeneration is the EMT (Griffith and Hay, 1992;Shuler et al 1991Shuler et al , 1992Kaartinen et al 1997;Nieto 2002;Nawshad et al 2004;Jin and Ding 2006;Yu et al 2009). We identified the molecular interaction between miR200b and Tgf-b-mediated Smad2 and Snail by reporter assay and overexpression of miR-200b.…”
Section: Mir-200b Modulates E-cadherin and Tgf-b-mediated Smad2 And Smentioning
confidence: 97%
“…Snail expression is activated by Tgf-b signaling (MartinezAlvarez et al 2004;Yu et al 2009), and Snail can then directly repress expression of E-cadherin (Carver et al 2001;Beltran et al 2008). Snail family genes are essential for correct palate formation and mutant mice of Snail family genes have cleft palate due to reduced apoptosis during palatogenesis (Murray et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…For all these mechanisms to occur properly in both mice and humans, the presence of transforming growth factor-␤ 3 (TGF-␤ 3 ) is crucial [Kaartinen et al, 1995;Proetzel et al, 1995;Lidral et al, 1998;Mitchell et al, 2001]. Its gene, together with those of TGF-␤ 1 and TGF-␤ 2 , is expressed in the mouse palate from E13 to E15 [Fitzpatrick et al, 1990;Pelton et al, 1990], where it triggers a phosphorylation cascade involving both SMAD-dependent and independent pathways [reviewed in Yu et al, 2009]. Experiments using Tgf-␤ 3 null mutant ( Tgf-␤ 3 -/-) mice demonstrated that SMAD2, but not SMAD3, is phosphorylated upon activation of TGF-␤ receptors and mediates most of the mechanisms causing palatal fusion [Cui et al, 2003[Cui et al, , 2005Shiomi et al, 2006].…”
mentioning
confidence: 99%
“…Then the complex translocates into the nucleus and binds the target gene to regulate gene expression in a cell type-specific and ligand dose-dependent manner. 18 TGF-A signaling pathway is correlated to the disappearance of MEE 10,19 and the proliferation of palatal mesenchymal cells. 20 To investigate the role of TGF-A signal pathway in palatogenesis, in vivo targeted mutations of individual gene were generated.…”
Section: Transforming Growth Factor a Familymentioning
confidence: 99%
“…The phenotypes range from early embryonic lethality to subtle phenotypes in adult mice. Specifically, some FGFs (FGF4, 8,9,10,15, and 18) knockout mice die during pregnancy or postnatal day, 44Y50 whereas others display different phenotypes. A strong association between FGFs and palatal anatomy suggested the role they played in palatal development.…”
Section: Fibroblast Growth Factormentioning
confidence: 99%